Percentile Degrees For Some Physical Fitness Components In Secondary School Female students in Baghdad - Altay, Duaa; Altay, Usama (Journal of Physical Education, 2018)
Percentile Degrees For Some Physical Fitness Components In Secondary School Female students in Baghdad The importance of the research lies in the importance of general health and physical fitness components in female secondary school students. The problem lies in the lack of physical fitness components percentile studies and the level of fat in female secondary school students. The researchers aimed at finding physical fitness components percentiles in secondary school students. The subjects were (4828) female secondary school students aged 13 – 15 years old. The researchers came up with percentile degree and recommended evaluating the percentile for physical fitness components in female students.